SOCIO-DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF LUNG CANCER PATIENTS IN NORTH MACEDONIA - Dimitrievska, Ljubica; Pavlovska, Irina; Stefanovska, Julijana; Stamenova, Aleksandra; Nehteparova, Meliha (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Lung cancer disease is one of the most common causes of mortality in the world, coming right after cardiovascular diseases. It is a big and is a special problem in the highly developed countries, especially in the USA, but also in developing countries. The reason for the research is the fact that the number of newly diagnosed and death cases from lung cancer is constantly growing, especially in the last few years. The aim of the study is to determine the influence of socio-demographic factors in the occurrence of lung cancer (gender, age, national and ethnic origin, place of residence) and smoking as the main risk factor associated with this neoplasm. The research is a descriptive study in which 82 patients with pathohistologically confirmed lung cancer participated. It was implemented at the Institute for Oncology and Radiotherapy at the clinical center in Skopje for a period of 3 months. A total of 82 patients were registered from Instutute for Oncology and Raditherapy in Skopje, North Macedonia who were diagnosed with primary lung cancer. Of all, 64.7% of them were males and 35.3% were females. Histologically, 51.2% had adenocarcinoma, 25.6 had squamous cell carcinoma, 20.7% had small cell carcinoma and 7.4% had no small cell carcinoma. It was observed that the proportion of females diagnosed with primary lung cancer is increasing. Patients get diagnosed at a later stage of the disease, which calls for screening and early detection of lung cancer. Keywords: Lung cancer, death, smoking, gender.